Antidepressant-like activities of extracts of the fungus Paecilomyces tenuipes M98. Issue 4 (2nd October 2019) - Li, Yaying; Han, Long; Lu, Tong; Noman, Muhammad; Qiang, Weidong; Lan, Xinxin; Gao, Tingting; Guo, Jinnan; Zhang, Xiaomei; Li, Haiyan; Yang, Jing; Du, Linna
ABSTRACT: Objective: Depression is an disease that seriously endangers the physical and mental health of human body. However, in view of the limitation of existing antidepressants, it's urgent to find new antidepressants from natural products. The aim of this study was to evaluate the effect of Paecilomyces tenuipes, which is an important entomogenous fungus in China. Methods: This research was intent to investigate the antidepressant actions of P. tenuipes M98 extracts using a battery of behavioural models including tail suspension test (TST) and forced swimming test (FST), 5-HTP-induced head twitch response and chronic unpredictable mild stress (CUMS) in mice. Results: Fifteen days treatment with aqueous and ethanol extracts signifificantly decreased the duration of immobility in TST and FST, without signifificant changes in locomotor activity. Moreover, chronic application of extracts for 21 days signifificantly improved the depressive-like behaviours of CUMS mice, including reduced body weight and sucrose preference and lengthened immobility time in TST and FST. In addition, extracts produced a signifificant increase in 5-hydroxytryptamine and dopamine, but not noradrenaline, levels in hypothalamus. These fifindings suggested that this action of P. tenuipes might be related to the regulation of serotonergic and dopaminergic systems, which were further confirmed via 5-HTP induced head-twitch test. In addition, P. tenuipes M98 extracts also displayed anti-oxidative effffects. Conclusion: P. tenuipes M98 extracts present excellent antidepressant-like activities, which might be explained by regulation of neurotransmitters and alleviation of oxidative stress.